(untitled) (Medico Legal Update, 2020)
Diabetes Mellitus is a fast-growing disorder in the current scenario commonly affecting all age groups especially elder groups. The high blood glucose can be kept in control with nutraceutical foods. The present study is aimed to formulate a nutritionally rich cookie with Costus igneus leaf extract and to determine the effect of cookie consumption on decreasing blood glucose levels in type 2 diabetic patients. Cookies made with Costus igneus leaf powder etc. were analyzed for proximate analysis and phytochemical analysis with standard procedures. A total of 30 Type-II diabetic patients were selected for the study whose demographic variables and blood glucose levels were measured on the first day and after 15 days, 30 days of cookies consumption. The proximate and physic-chemical analysis showed cookies contain high amount of secondary metabolites including antioxidant compounds. Among the 30 study subjects, the mean levels of FBS and PBS were decreased significantly in all the four groups from day 0 to day 30 which indicates that C.igneus cookies consumption had good effect in reducing the blood glucose levels. However the HbA1C has been decreased by one unit in all the four study groups. The cookies made with Costus igneus plant material have good antimicrobial, antioxidant and antidiabetic activities and can be used as a therapeutic and functional food source for the treatment of overweight, obesity and diabetes.